Probing hadron properties with scattering - Maležič, Marko (Matrika, 2023)
An important study in quantum mechanics is the study of scattering. By employing scattering, it is possible to find new states that can be bound or short-lived. In this paper, We will formally derive the scattering amplitude for scattering on the potential and express it with a phase shift. Although this approach is quite restrictive, it still produces important results. It renders information on the interaction between particles and reveals properties of bound states and resonances. After the theoretical formalism, We will give some examples of states studied numerically and experimentally. Although scattering is present in many fields of physics, We will focus on examples from hadron particle physics.
Keywords: fizika osnovnih delcev; hadroni; hadrons; kvantna mehanika; physics of elementary particles; quantum mechanics; scattering; sipanje